Resposta da resistência insulínica de mulheres menopausadas ao protocolo de exercício intervalado em esteira ergométrica - Nakagaki, Mariana Santoro [UNESP] (2015)
Menopause is a normal part of the aging process of the woman, which is marked by permanent amenorrhea. It is an event that results from changes in levels of female sex hormones and consequently promotes a series of physiological changes that culminate in the predisposition to the emergence or worsening of chronic diseases. The increasing prevalence of type 2 diabetes mellitus (T2DM) is related to the growth of obesity and about 90% of T2DM is attributed to excess weight. The identification of diseases and their risk factors affecting women during aging allow the introduction of preventive measures to prevent or delay its onset, with consequent reduction in the incidence of mortality and thus increase quality of life programs. It is known that changes in lifestyle result in decreased DM and that physical exercise is an important nonpharmacological tool in fighting this disease. Physically active patients with T2DM improve insulin sensitivity by increasing muscle mass, increasing blood flow, increasing in density of insulin receptors, greater uptake and utilization of glucose by skeletal muscle. The reduction of adipose tissue induced by physical training in patients with DM also improves insulin sensitivity and glucose tolerance. The interval exercise protocol (high intensity) requires greater muscle fiber recruitment and the depletion of muscle glycogen stores occurs more quickly in all types of muscle fibers. Thus, there are better muscle glucose uptake and resynthesize of glycogen after exercise if compared with exercise of low or moderate intensity. Furthermore, increased recruitment of muscle fiber can lead to metabolic adaptations in more muscle fibers, maintenance of the effects on metabolic control and insulin sensitivity. The high-intensity exercise, so can show advantages in the prevention and treatment of insulin resistance and T2DM